2013
DOI: 10.1107/s0907444913004472
|View full text |Cite
|
Sign up to set email alerts
|

New features of vault architecture and dynamics revealed by novel refinement using the deformable elastic network approach

Abstract: The vault particle, with a molecular weight of about 10 MDa, is the largest ribonucleoprotein that has been described. The X-ray structure of intact rat vault has been solved at a resolution of 3.5 Å [Tanaka et al. (2009), Science, 323, 384-388], showing an overall barrel-shaped architecture organized into two identical moieties, each consisting of 39 copies of the major vault protein (MVP). The model deposited in the PDB includes 39 MVP copies (half a vault) in the crystal asymmetric unit. A 2.1 Å resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 35 publications
(54 reference statements)
7
19
0
Order By: Relevance
“…Vaults did not appear to adopt a preferred orientation within the granule beds, but a few vaults appeared to interact with granules at their caps, or by opening up at their waist region (Fig. 6), observations consistent with previous reports [8, 26]. Given the previously reported localization of vPARP to the waist region of the vault [1], it is possible that the granules are enzymatically targeted by vault-associated vPARP.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Vaults did not appear to adopt a preferred orientation within the granule beds, but a few vaults appeared to interact with granules at their caps, or by opening up at their waist region (Fig. 6), observations consistent with previous reports [8, 26]. Given the previously reported localization of vPARP to the waist region of the vault [1], it is possible that the granules are enzymatically targeted by vault-associated vPARP.…”
Section: Discussionsupporting
confidence: 90%
“…2, panels a, e). These observations underscore the role of the midsection in mediating vault dynamics, and are not surprising since the twofold axis at the vault waist region delineates the half-vault structures that comprise the full particle [8, 26]. Previous work suggested that within cells half-vaults could exchange with each other by separating at the midsection [27], but we did not see structures consistent with this type of complex dynamic.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…5b). The structure and some of the details of the function of these fascinating vault-like particles have been revealed by the groups of Tsukihara and coworkers in Japan (Tanaka et al, 2009) and Fita, Verdaguer and coworkers in Barcelona, Spain (Querol-Audí et al, 2009;Casañ as et al, 2013).…”
Section: Figurementioning
confidence: 96%
“…An important characteristic of many systems is symmetry, i.e., the electron scattering intensity is invariant under the operations of a symmetry group. On 05 November 2017, the Protein Data Bank [40] contained 130,005 structures in seven symmetry classes: Asymmetric (60.198%), Cyclic C n (31.020% with n ranging from 2 to 39 [41], [42] ), Dihedral D n (7.517% with n ranging from 2 to 48 [43]), Icosahedral I (0.491%), Tetrahedral T (0.280%), Octahedral O (0.248%), and Helical (0.245%). We focus on the rotational point groups, which are I, O, T , C n , and D n , and which have 60, 24, 12, n, and 2n symmetry operations, respectively.…”
Section: B Symmetrymentioning
confidence: 99%